FAKTOR-FAKTOR YANG MEMPENGARUHI PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN NARKOTIKA DI KALANGAN REMAJA (STUDI PADA KEPOLISIAN DAERAH BALI) - I Gede Putu Mantra; Ni Ketut Sri Ratmini; I Nyoman Adhi Harsa Jaya (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
One group that is vulnerable to being carried away by the flow of narcotics abuse is teenagers, this is because teenagers are at the stage of seeking identity, adolescence is a transition to adulthood. The family environment has a very important role in the formation of adolescent personality. Narcotics abuse among adolescents has become a national threat that needs to get serious attention by all elements of the nation. Lack of communication and openness in the family is one of the factors that participate in narcotics abuse among adolescents.This type of research is empirical juridical research, which is a type of research that uses facts that occur in reality in society, the nature of research in this study is descriptive. While the purpose of this study, is to find out the factors that influence law enforcement against narcotics abuse among adolescents.Law enforcement against narcotics abuse among adolescents is influenced by several factors such as, legal substance, legal structure and legal culture.